2022
DOI: 10.3389/fpubh.2022.820727
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Laboratory Outcomes in HIV-1 and HTLV-1/2 Coinfection: A Systematic Review

Abstract: AimTo perform a systematic review to describe the available findings on clinical outcomes in HIV-1 and HTLV-1/HTLV-2 co-infected individuals since 1995.DesignThis Systematic Review used PECO criteria follow by PRISMA reporting guidelines and registered as CRD42021279062 (Prospero database). The Newcastle-Ottawa Scale assessed the methodological quality of included studies.Data Collection and AnalysisA systematical search in PubMed/MEDLINE, Embase, Web of Sciences databases for cross-sectional, case-control, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Several factors are involved in HTLV-1 transmission and probably to the evolution to related diseases in mono-infected and HIV-1/HTLV-1 co-infected individuals. Clinical aspects and outcomes in persons co-infected with both retroviruses were recently summarized in the review [37]. And as previously shown, co-infection with both retroviruses may lead to rapid evolution to AIDS and development of opportunistic infections in the absence of ART [38,39].…”
Section: Discussionmentioning
confidence: 94%
“…Several factors are involved in HTLV-1 transmission and probably to the evolution to related diseases in mono-infected and HIV-1/HTLV-1 co-infected individuals. Clinical aspects and outcomes in persons co-infected with both retroviruses were recently summarized in the review [37]. And as previously shown, co-infection with both retroviruses may lead to rapid evolution to AIDS and development of opportunistic infections in the absence of ART [38,39].…”
Section: Discussionmentioning
confidence: 94%
“…HIV and HTLV belong to the Retroviridae family and share genomic and epidemiological characteristics. Moreover, a recent meta-analysis showed that individuals with HIV and HTLV-I coinfection have accelerated HIV progression, worse survival, and a high incidence of HAM/TSP, peripheral neuropathy, encephalopathy, and opportunistic infections, such as scabies, candidiasis, and strongyloidiasis [76,77]. HTLV-1 activates CD4+ T cells, and Tax upregulates HIV-1 infection [78].…”
Section: Coinfection 421 Hivmentioning
confidence: 99%
“…HIV and HTLV belong to the Retroviridae family and share genomic and epidemiological characteristics. Moreover, a recent meta-analysis showed that HIV and HTLV-I-coinfected subjects have accelerated HIV progression, worse survival, and a high frequency of developing HAM/TSP, peripheral neuropathy, encephalopathy, and opportunistic infections, such as scabies, candidiasis, and strongyloidiasis [76,77]. HTLV-1 activates CD4+ T cells, and Tax upregulates HIV-1 infection [78].…”
Section: Hivmentioning
confidence: 99%